Clinical Profile and Outcome of Patients using Botulinum Toxin for Cosmetic Purposes: A Cross-sectional Study - Reshmi Subramaniam; Vani Vasanth; BS Chandrasekhar; Asida Mohamed Ashraf; Ashwini Babu; Neetha Latha (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Botulinum toxin injection has become ubiquitous in the treatment of wrinkles. It is less invasive and easy to perform, with almost immediate effects. Although it is the most common non surgical cosmetic procedure performed in many parts of the world, accurate figures of its increasing trend in India need to be unraveled as well. Aim: To analyse the clinical profile, outcomes, indications, and nature of revisits among patients seeking Botulinum toxin injections for cosmetic indications. Materials and Methods: A cross-sectional observational study was conducted at a tertiary care centre, Department of Dermatology, Cutis Academy of Cutaneous Sciences, Bengaluru, Karnataka, India, for six months between November 2018 and April 2019 among 80 consecutive patients who received Botulinum toxin injection A for cosmetic purposes. The collected data included age, gender, indication, the number of units of Botulinum toxin used, and the profile of patients seeking revisits. The data was recorded and analysed using Statistical Product and Service Solutions (SPSS) version 23.0. Results: The average age for treatment among females was 38 years, while among males, it was 35.5 years. Females, comprising 61 (76%), outnumbered men by a factor of three. The single most common indication for Botulinum toxin injection among females was Crow’s feet, accounting for 26 (43%), and among females below 40 years, it was Masseter hypertrophy in 13 (21%). The most common indication among men was Glabellar line correction in 10 (53%). Other indications included the Nefertiti lift, Marionette lines, Popply chin, Brow lift, and Gummy smile. Women revisited the clinic three times more often than men. Among women, Crow’s feet correction was the most common reason for revisits. The number of units of Botulinum toxin needed was found to be higher in males for Glabellar lines and in older individuals for Masseter Hypertrophy. Conclusion: Women are more receptive to cosmetic facial Botulinum toxin injections and revisit more frequently than men. Adverse effects were mild and self-limiting. Upper-face Botulinum toxin injections appear to be the preferred indication in both genders. More epidemiological studies detailing the profile of patients seeking aesthetic Botulinum toxin injections are needed to better understand patients’ needs and concerns, offer preprocedure counselling, manage their expectations, and provide customised services.